Paramagnetic Structures within a Microfluidic Channel for Enhanced Immunomagnetic Isolation and Surface Patterning of Cells - Sun, Chen (Sci Rep, 2016)
In this report, we demonstrate a unique method for embedding magnetic structures inside a microfluidic channel for cell isolation. We used a molding process to fabricate these structures out of a ferrofluid of cobalt ferrite nanoparticles. We show that the embedded magnetic structures significantly increased the magnetic field in the channel, resulting in up to 4-fold enhancement in immunomagnetic capture as compared with a channel without these embedded magnetic structures. We also studied the spatial distribution of trapped cells both experimentally and computationally. We determined that the surface pattern of these trapped cells was determined by both location of the magnet and layout of the in-channel magnetic structures. Our magnetic structure embedded microfluidic device achieved over 90% capture efficiency at a flow velocity of 4 mm/s, a speed that was roughly two orders of magnitude faster than previous microfluidic systems used for a similar purpose. We envision that our technology will provide a powerful tool for detection and enrichment of rare cells from biological samples.